2013
DOI: 10.1155/2013/296019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Fields on Osteogenesis of Human Alveolar Bone-Derived Mesenchymal Stem Cells

Abstract: This study was performed to investigate the effects of extremely low frequency pulsed electromagnetic fields (ELF-PEMFs) on the proliferation and differentiation of human alveolar bone-derived mesenchymal stem cells (hABMSCs). Osteogenesis is a complex series of events involving the differentiation of mesenchymal stem cells to generate new bone. In this study, we examined not merely the effect of ELF-PEMFs on cell proliferation, alkaline phosphatase (ALP) activity, and mineralization of the extracellular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
0
45
0
1
Order By: Relevance
“…It has been demonstrated that LIPUS exposure increased cyclooxygenase-2 mRNA expression which leads to an increase in PGE2 (prostaglandin E2) and plays an essential role in the osseointegration of dental implants [4244]. Another research showed that extremely low frequency pulsed electromagnetic fields (ELF-PEMFs) could enhance early cell proliferation in hABMSCs-mediated osteogenesis and accelerate the osteogenesis [45]. VEGF is a key regulator for angiogenesis which is essential to fracture healing [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that LIPUS exposure increased cyclooxygenase-2 mRNA expression which leads to an increase in PGE2 (prostaglandin E2) and plays an essential role in the osseointegration of dental implants [4244]. Another research showed that extremely low frequency pulsed electromagnetic fields (ELF-PEMFs) could enhance early cell proliferation in hABMSCs-mediated osteogenesis and accelerate the osteogenesis [45]. VEGF is a key regulator for angiogenesis which is essential to fracture healing [46].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the day 21, formalin-fixed cells were washed in 50% isopropanol and stained with oil Red for 15 min and observed by a light microscope [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Manjhi et al (2013) reported that chronic (2 h/d × 8 wk) EMF exposure (17.96 μT, 50 Hz) to spinal cord injury (SCI) in rats is effective in attenuating SCI-induced osteoporosis [16]. In a study by Lim et al (2013), it was demonstrated that ELF-PEMF significantly cause the alteration of osteogenesis-related genes expression in human alveolar bone-derived mesenchymal stem cells [17]. Yan et al (2015) indicated that 0.6 mT, 50 Hz PEMF stimulates both proliferation and osteogenic differentiation of rat calvarial osteoblasts [14].…”
Section: Introductionmentioning
confidence: 99%
“…For an in vitro study, four groups were chosen and labeled as follows: 1) Glass, i.e., the group cultured on glass substrates as a control; 2) Glass+PEMFs, the group cultured on glass substrates and irradiated by PEMFs; 3) RGO, the group cultured on RGO substrates; and 4) RGO+PEMFs, the group cultured on RGO substrates and irradiated by PEMFs. The PEMFs were irradiated using a solenoid following the method described in our previous study . A function generator was used to generate square wave electric signals of ±5 V with a frequency of 50 Hz and a 50% duty cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, EMFs have been reported to modulate cell proliferation, DNA replication, wound healing, cytokine expression, and cell differentiation . In particular, PEMFs enhanced both the osteogenic differentiation and neurogenic differentiation of mesenchymal stem cells (MSCs) . In addition, EMFs enhanced the direct reprogramming of mouse embryonic fibroblasts into induced pluripotent stem cells .…”
Section: Introductionmentioning
confidence: 99%